Enforcement orders - Perla Velaochaga, Ernesto (1972)
This paper focuses on executive titles. The author develops its concept, characteristics, types, prescription period and regulatory framework. In this connection, the article briefly covers the executive titles covered by the regulations and their characteristics: i) the express or formal judicial confession; ii) public documents; iii) private documents; iv) bills of exchange and orders; v) vouchers and promissory notes; vi) checks; vii) bearer certificates; viii) knowledge protested against the captain and endorsers; ix) letters of lading protested; and, x) enforcement by collection of censuses and leases.